2021
DOI: 10.3389/fpsyt.2021.790732
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Cortical Activation Patterns Among Chinese-Speaking Schizophrenia Patients During Category and Letter Verbal Fluency Tasks Revealed by Multi-Channel Functional Near-Infrared Spectroscopy

Abstract: Background: Functional near-infrared spectroscopy (fNIRS) has many advantages over other neuroimaging modalities for routine measurement of task-dependent cortical activation, but most fNIRS studies of schizophrenia have used letter fluency tasks (LFTs). Further, performances on category fluency tasks (CFTs) and LFTs may be distinct in Chinese patients due to the unique semantic features of Chinese written characters. To identify unique disease biomarkers measurable by fNIRS in Chinese schizophrenia patients, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…This is inconsistent with a former VFT study on adult patients with first-episode SCZ (32); they found that although oxy-Hb concentration increase in the patient group was lower than in HC, the patients showed significantly increased frontotemporal activities during the VFT in most channels. Similar frontotemporal activation pattern was also found in adult patients with chronic SCZ (22,33,34). However, in the present study, the patient group showed no obvious increase in oxy-Hb concentration after the 60-s task period started, and even a decrease of oxy-Hb concentration was found in some channels (Figure 3).…”
Section: Atypical Cortical Activity In Sczsupporting
confidence: 85%
See 1 more Smart Citation
“…This is inconsistent with a former VFT study on adult patients with first-episode SCZ (32); they found that although oxy-Hb concentration increase in the patient group was lower than in HC, the patients showed significantly increased frontotemporal activities during the VFT in most channels. Similar frontotemporal activation pattern was also found in adult patients with chronic SCZ (22,33,34). However, in the present study, the patient group showed no obvious increase in oxy-Hb concentration after the 60-s task period started, and even a decrease of oxy-Hb concentration was found in some channels (Figure 3).…”
Section: Atypical Cortical Activity In Sczsupporting
confidence: 85%
“…Concerning the VFT performance is associated with the difficulty of task ( 36 ), the phonological fluency task used might be equally difficult for the adolescents with first-episode SCZ and HCs. Some researchers proposed that the category fluency task (CFT) might be superior for the evaluation of Chinese-speaking patients with psychiatric disorders ( 34 ). Thus, further studies on potential inter-task effects in adolescents are still needed.…”
Section: Discussionmentioning
confidence: 99%
“…The symptoms (states) are identified and analyzed in the way of full-channel waveform, phase changes, and waveform composition ratios, and six typical waveforms (see Figure 2 ) with clinical significance are summarized to correlate with the typical symptom among various mental disorders ( 17 ). It has helped in the diagnosis of bipolar disorder and unipolar depression ( 15 ), major depressive disorder and generalized anxiety disorder ( 16 ), schizophrenia ( 28 ), and other mental disorders.…”
Section: Multi-cognitive Tasks Paradigmmentioning
confidence: 99%
“…A meta-analysis reported that category fluency and letter fluency are impaired in patients with schizophrenia [ 9 ]. A lack of verbal fluency is considered a predictor of psychosis, whereas, in patients with chronic schizophrenia, the symptoms are fixed [ 10 ]. In another study, a category fluency task was administered to adolescent patients with schizophrenia and was found to be significantly correlated with other cognitive functions and psychiatric symptoms, particularly those related to verbal learning, working memory, and processing speed.…”
Section: Introductionmentioning
confidence: 99%